Corona monitoring nationwide (RKI-SOEP-2): Seroepidemiological study on the spread of SARS-CoV-2 across Germany - Susanne Bartig; Herbert Brücker; Hans Butschalowsky; Christian Danne; Antje Gößwald; Laura Goßner; Markus M. Grabka; Sebastian Haller; Doris Hess; Isabell Hey; Jens Hoebel; Susanne Jordan; et al. (Journal of Economics and Statistics, 2023)
SARS-CoV-2, the coronavirus, spread across Germany within just a short period of time. Seroepidemiological studies are able to estimate the proportion of the population with antibodies against SARS-CoV-2 infection (seroprevalence) as well as the level of undetected infections, which are not captured in official figures. In the seroepidemiological study Corona Monitoring Nationwide (RKI-SOEP-2), biospecimens and interview data were collected in a nationwide population-based subsample of the Socio-Economic Panel (SOEP). By using laboratory-analyzed blood samples to detect antibodies to the SARS-CoV-2 virus, we were able to identify a history of vaccination or infection in study participants. By combining these results with survey data, we were able to identify groups within the population that are at increased risk of infection. By linking the RKI-SOEP-2 survey data with data from other waves of the SOEP survey, we will be able to examine the medium- to long-term impacts of the COVID-19 pandemic, including effects of long COVID, in diverse areas of life. Furthermore, the data provide insight into the population's willingness to be vaccinated as well as related attitudes and conditions. In sum, the RKI-SOEP-2 survey data offer a better understanding of the scope of the epidemic in Germany and can help in identifying target groups for infection control in the present and future pandemics.
Keywords: I12; I19; C89; 330; COVID-19; SARS-CoV-2; seroepidemiological study; seroprevalence; SOEP; vaccine status; willingness for vaccination